THE GOD PARTICLE AS ‘KNOWING THE MIND OF GOD’: Moving from a Quantum Singularity towards a Cosmic Singularity - Mathew Chandrankunnel (Journal of Dharma, 2012)
An unprecedented and an overwhelming enthusiasm were indeed exhibited by the print and electronic media on the discovery of the God particle. Media, both in India and abroad celebrated the event with attractive headlines and discussions with experts and thus fired even the imagination of the common people. Therefore, it would be worth to ponder over the deeper meaning and significance of this discovery and its probable repercussions in our life and the relevance for religion, especially for a Christian life in terms of reason and faith.